Detection Trisomy Chromosome 12 in Relation to the Expression Of Cd38 and Light Chain Restriction in Chronic Lymphocytic Leukemia Patients - Hiba Hamid Hashim; Subeh Salim Abdulateef; Mazin Essa Menaf (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Chronic lymphocytic leukemia is a malignancy of mature B cells where there is progressiveaccumulation of leukemic cells. The genetic factors have been found to play a role, deletions of the long armof chromosome 13, specifically involving band 13q14 (del(13q14)), represent the single most frequentlyobserved cytogenetic aberration in CLL, followed by trisomy 12 ,del 11q22, del 6q21, del 17p13, and 14q.Objectives: To detect the structural abnormalities on chromosome 12 (trisomy 12 in patients with CLLby using FISH technique; To investigate the relation of this chromosomal abnormalities with with theexpression of CD38 and light chain restriction .Patients, Materials and Methods: 1. This cross-sectional study was conducted from February 25, 2018 toDecember 15, 2019. Fifty newly diagnosed adult patients with CLL were enrolled in this study. 2. Each patientwas assessed at the time of admission, full clinical and laboratory data were obtained from patient’s hospitalrecords. Three ml of fresh blood sample were taken from each patient at admission. Upon confirmation ofCLL diagnosis, samples were taken to FISH unit for blood preparation which includes two steps in twodays, the first day to separate lymphocyte cells from another component of blood and second-day washingsamples and stored till slide preparation. Slide preparation done in the 1st day and using dual color geneprobe and slide reading in the second day by fluorescent microscope. The collected data were computerizedand statistically analyzed using the SPSS program (Statistical Package for Social Science) version 23.Result: The median age of the patients was 64 years and the range was 45-76 years. Among 50 patientsstudied, 18 patients were females, representing (36%) and 32 patients were males representing (64%). Male:female ratio 1.8:1. Trisomy chromosome12 was found 15 out of 50 patients with CLL, representing 30%.Conclusion:1.In the current study,15 out of 50 CLL patients (30%)present with trisomy chromosome 12 ina sample of Iraqi adult CLL patients.2. trisomy CH 12 patients show significant relation with light chainrestriction .